The Isolation of Online Adjunct Faculty and its Impact on their Performance - Dolan, Véra (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
Using a grounded theory qualitative research approach, this article examines the experiences of 28 adjunct faculty members who work at the same university, exploring their views on whether periodically meeting face-to-face with management and peers has the potential to affect their motivation on the job and consequently the quality of education they provide to students. A few management representatives also shared their perspectives on the phenomenon; this enabled the researcher to compare the views of these two populations on whether face-to-face contact among faculty enhances teaching performance. The results of this study suggest a few issues that online schools must address in their efforts to improve adjuncts’ sense of affiliation and loyalty to their institution, which in turn will positively affect student retention levels. The main issues of concern to adjunct faculty are (a) inadequate frequency and depth of communication, regardless of the means used, whether online or face-to-face; (b) lack of recognition of instructors’ value to the institution; and (c) lack of opportunities for skill development.